PENINGKATAN KESEHATAN ANAK MELALUI LAYANAN Khitanan: PROGRAM PELAYANAN MASYARAKAT DI DESA CAHAYA BARU KABUPATEN BARITO KUALA INDONESIA - Alfiannor, M.; Susilo, Yudi Hardi; Ulfah, Maria; Niah, Rakhmadhan; Aisyah, Noor; Riski, Akhmad; Normilawati, Normilawati; Nurjihan, Lu’lu; Kurniawan, Henny; Wahyudi, Wahyudi; Rustandi, Tedi; Ma’ruf, Muhammad; Wahyuni, Amaliyah; Ariani, Novia; Fawwazi, Muhammad Hafizh Abiyyu Fathin; Yumassik, Abdul Mahmud; Widodo, Arif Nur; Prihandiwati, Erna; Susanto, Yugo (Sekolah Tinggi Ilmu Kesehatan ISFI Banjarmasin, 2025)
Background: Child health is essential for human resource development, especially in communities with limited health services. One preventive measure that can be taken to maintain genital hygiene is circumcision. This preventive measure reduces the risk of urinary tract infections and sexually transmitted diseases. However, to carry out child circumcision independently, there are some financial problems in Cahaya Baru Village, Jejangkit District, Barito Kuala Regency. Methods: This activity involved children from Cahaya Baru Village. Participant screening, health instructions, circumcision procedures carried out by medical professionals, post-procedure medication administration, and medication use instructions were all methods used in the implementation. The Indonesian Red Crescent (BSMI) of South Kalimantan, the Barito Kuala District Health Office, the Jejangkit District Health Center, and the Cahaya Baru Village government were involved in this project. Results and discussion: Forty participants successfully received a safe and controlled circumcision procedure. Before the procedure, all participants underwent a screening process and received health instructions. There were no significant complications post-circumcision, and all participants received pain relievers and antibiotics for healing. In addition, DAGUSIBU training increased community understanding of proper drug use. Active participation of various parties ensured that activities ran smoothly and increased synergy in community-based health services. Conclusion: Mass circumcision activities in Cahaya Baru Village showed that multi-sector collaboration-based programs can improve community access to basic health services. This program was successful thanks to participation, trained medical personnel, and health education. Similar efforts are expected to be carried out sustainably to increase the positive effects on community health welfare.